Gestalt Theory Rearranged: Back to Wertheimer - Guberman, Shelia (Frontiers in Psychology, 2017)
Abstract Wertheimer’s seminal paper of 1923 was of gerat influence in psychology and other sciences. Wertheimer also emphasized the weaknesses of the newborn Gestalt theory: too many basic laws, and the ambiguity of definitions. At the same time, the paper contained potential solutions to these problems, in the form of a number of very important ideas, some of which were presented implicitly: perception through imitation, communicative nature of linear drawings and writings, transfer from the visual domain to motor domain, linguistic interpretation of the Gestalt. In this paper it will be shown that based on these ideas the Gestalt theory can be rearranged so that the main notions can be well defined, and the general principle of Gestalt perception, which overarches all known laws and unifies different Gestalt phenomena (the imitation principle) can be introduced. The presented model of Gestalt perception is supported by fundamental neurophysiological data – the mirror neurons phenomenon and simulation theory.